Preparation and characterisation of calcium oxide from gypsum based compound for transesterification of waste cooking oil - Neshabran, Ramachandran (2018)
In the present work, gypsum (calcium sulphate dihydrate), from chemical supply company (laboratory grade gypsum) and industrial waste (waste gypsum) was utilised to produce calcium oxide (CaO). The waste gypsum (red gypsum) was obtained from Huntsmann Tioxide (M) Sdn. Bhd. Terengganu, Malaysia. Waste cooking oil was used to produce FAME with methanol via transesterification utilising CaO from waste gypsum as heterogeneous catalyst. Two different methods were employed to convert gypsum to CaO. In the first method, two-step reaction method, laboratory grade gypsum and waste gypsum were utilised separately, where it was chemically treated to produce calcium hydroxide. Later, the calcium hydroxide was calcined and decomposed to CaO at much lower temperatures than prior methods. For the second method, a modified carbothermal reduction method was utilised. Two different static gaseous environments were used (to study the effect of different gas) instead of continuous gas flow (to study the effect of static environment) in this modified method. The catalyst zinc oxide for carbothermal reduction process was used to increase CaO. The samples of CaO preparation were sent for XRD, TGA and FESEM-EDX analysis. Transesterification of waste cooking oil and methanol (MeOH) using CaO from waste gypsum (prepared via two-step method) as a heterogeneous catalyst was done at a fixed temperature of 60°C and fixed 12:1 MeOH:oil molar ratio; to produce FAME. Effect on ester content of CaO catalyst amount variation (3 wt. % and 5 wt. %) and reaction duration (5h and 7h) was studied. The ester content was calculated according EN14214 from GC-FID analysis. The quality of FAME produced and purified was analysed using ICP-MS and CHNOS analyser. Engine testing was conducted using B10 biodiesel blend made from FAME produced. The X-Ray Diffraction diffractograms from CaO preparation samples were analysed using Match! software from Crystal Impact with Crystallography Open Database. From the diffractograms of two-step reaction method done on laboratory grade gypsum, it is shown that the complete absence of any other peaks except CaO peaks is evident for almost 100% conversion of laboratory grade gypsum to CaO. From the diffractograms of two-step reaction method done on waste gypsum, it was calculated that the CaO content was at 86.45%. This two-step conversion method has safely liberated the sulphate group as sodium sulphate, from gypsum, which gives rise to sulphur dioxide gas, when gypsum is converted to calcium oxide through carbothermal reduction method. The modified carbothermal reaction proved to be advantageous as well. The sulphur oxide gas produced in this route was further reacted with carbon or carbon monoxide and reduced to elemental sulphur. The highest CaO content, 31.80% was obtained from the static nitrogen environment; activated carbon to gypsum ratio of 20:1, with 2 wt. % zinc oxide catalyst. By using CaO from waste gypsum as a catalyst it was identified that transesterification of waste cooking oil with methanol gave highest ester content of 97.72% for 3 wt. % and 5h variation. The ICP-MS results revealed that sonication and filtration using activated carbon are needed twice to reduce the cation leachate (especially Ca2+) in order to fit EN 14214’s “Group II metals” content and sulphur content. The engine testing using B10 blend biodiesel blend made using produced FAME showed that threatening carbon monoxide reduced by 0.03% volume to 0.05% volume compared to petro-diesel.